Neuroprotective Strategies for Neurological Disorders by Natural Products: An update - Rehman, Muneeb U.; Wali, Adil F.; Ahmad, Anas; Shakeel, Sheeba; Rasool, Saiema; Ali, Rayeesa; Rashid, Shazada Mudasir; Madkhali, Hassan; Ganaie, Majid Ahmad; Khan, Rehan (Current Neuropharmacology, 2019)
Nature has bestowed mankind with surplus resources (natural products) on land and water. Natural products have a significant role in the prevention of disease and boosting of health in humans and animals. These natural products have been experimentally documented to possess various biological properties such as antioxidant, anti-inflammatory and anti-apoptotic activities. In vitro and in vivo studies have further established the usefulness of natural products in various preclinical models of neurodegenerative disorders. Natural products include phytoconstituents, like polyphenolic antioxidants, found in herbs, fruits, nuts, vegetables and also in marine and freshwater flora. These phytoconstituents may potentially suppress neurodegeneration and improve memory as well as cognitive functions of the brain. Also, they are known to play a pivotal role in the prevention and cure of different neurodegenerative diseases, such as Alzheimer’s disease, epilepsy, Parkinson’s disease and other neuronal disorders. The large-scale neuro-pharmacological activities of natural products have been documented due to the result of either the inhibition of inflammatory processes, or the up-regulation of various cell survival proteins or a combination of both. Due to the scarcity of human studies on neuroprotective effects of natural products, this review focuses on the various established activities of natural products in in vitro and in vivo preclinical models, and their potential neuro-therapeutic applications using the available knowledge in the literature.
Keywords: nutraceuticals